2021
DOI: 10.3390/jcm10184190
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Increase in Thrombogenicity and Its Correlation with von Willebrand Factor

Abstract: Endothelial cells that cover the lumen of all blood vessels have the inherent capacity to express both pro and anticoagulant molecules. However, under normal physiological condition, they generally function to maintain a non-thrombogenic surface for unobstructed blood flow. In response to injury, certain stimuli, or as a result of dysfunction, endothelial cells release a highly adhesive procoagulant protein, von Willebrand factor (VWF), which plays a central role in formation of platelet aggregates and thrombu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 203 publications
0
10
0
Order By: Relevance
“…Von Willebrand factor (VWF) is a multisubunit protein that anchors platelets to subendothelial collagen. It serves as a carrier protein for the VIII factor in plasma, and endothelial cell release of VWF plays an essential role in the formation of platelet aggregates and thrombosis and is closely associated with aging ( Alavi, Rathod & Jahroudi, 2021 ). We found that VWF was upregulated in the AAA (aged) group (compared with the normal (aged) group or the AAA (aged) group), suggesting that it might be associated with aging and AAA formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Von Willebrand factor (VWF) is a multisubunit protein that anchors platelets to subendothelial collagen. It serves as a carrier protein for the VIII factor in plasma, and endothelial cell release of VWF plays an essential role in the formation of platelet aggregates and thrombosis and is closely associated with aging ( Alavi, Rathod & Jahroudi, 2021 ). We found that VWF was upregulated in the AAA (aged) group (compared with the normal (aged) group or the AAA (aged) group), suggesting that it might be associated with aging and AAA formation.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, VWF was found to be expressed in aneurysm tissue and colocalized with hepatocyte growth factor (HGF) in the most severe part of the aneurysm-injured wall ( Shintani et al, 2011 ). As age increases, VWF levels increase significantly, and thrombosis events increase significantly ( Alavi, Rathod & Jahroudi, 2021 ). Fibrinogen is a vital protein involved in the processes of coagulation and hemostasis and plays a crucial role in the process of AAA formation, and fibrinogen has been proven to be a plasma biomarker of AAA formation and progression ( Sundermann et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, there was no significant difference in plasma VWF between the RVO and age-matched controls at the baseline. Several researchers have reported that plasma VWF increased not only in patients with hypertension and arteriosclerosis but also in healthy individuals with aging [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, plasma VWF was not significant between the RVO group and age-matched controls at baseline. Several researchers have reported that plasma VWF increases not only in patients with hypertension and arteriosclerosis but also in healthy individuals with aging [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%